Lipid-Based Poly(I:C) Adjuvants Strongly Enhance the Immunogenicity of SARS-CoV-2 Receptor-Binding Domain Vaccine. Issue 1 (20th January 2023) - Wu, Yixin; Meng, Liuxian; Zhang, Huicong; Hu, Shun; Li, Fusheng; Yu, Yingjie
Abstract: Background: The outbreak of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has greatly threatened public health. Recent studies have revealed that the spike receptor-binding domain (RBD) of SARS-CoV-2 is a potent target for vaccine development. However, adjuvants are usually required to strengthen the immunogenicity of recombinant antigens. Different types of adjuvants can elicit different immune responses. Methods: We developed an RBD recombinant protein vaccine with a polyriboinosinic acid–polyribocytidylic acid [poly(I:C)] adjuvant to evoke a strong immune response. The delivery of poly(I:C) was optimized in two steps. First, poly(I:C) was complexed with a cationic polymer, poly-l -lysine (PLL), to form poly(I:C)–PLL, a polyplex core. Thereafter, it was loaded into five different lipid shells (group II, III-1, 2-distearoyl-sn-glycero-3-phosphocholine [DSPC], III-1, 2-dioleoyl-sn-glycero-3-phosphoethanolamine [DOPE], IV-DOPE, and IV-DSPC). We performed an enzyme-linked immunosorbent assay and enzyme-linked immunosorbent spot assay to compare the ability of the five lipopolyplex adjuvants to enhance the immunogenicity of the SARS-CoV-2 RBD protein, including humoral and cellular immune responses. Finally, the adjuvant with the highest immunogenicity was selected to verify the protective immunity of the vaccine through animal challenge experiments. Results: Recombinant RBD protein has low immunogenicity. The different adjuvants we developed enhanced the immunogenicity of the RBD protein in different ways. Among the lipopolyplexes, those containing DOPE (III-DOPE and IV-DOPE) elicited RBD-specific immunoglobulin G antibody responses, and adjuvants with four components elicited better RBD-specific immunoglobulin G antibody responses than those containing three components ( P < 0.05). The IC50 and IC90 titers indicated that the IV-DOPE lipopolyplex had the greatest neutralization ability, with IC50 titers of 1/117, 490. Furthermore, in the challenge study, IV-DOPE lipopolyplex protected mice from SARS-CoV-2 infection. On the fourth day after infection, the average animal body weights were reduced by 18.56% (24.164 ± 0.665 g vs. 19.678 ± 0.455 g) and 0.06% (24.249 ± 0.683 g vs. 24.235 ± 0.681 g) in the MOCK and vaccine groups, respectively. In addition, the relative expression of viral RNA in the vaccinated group was significantly lower than that in the MOCK group ( P < 0.05). Interstitial inflammatory cell infiltration was observed in the MOCK group, whereas no obvious damage was observed in the vaccinated group. Conclusions: The IV-DOPE–adjuvanted SARS-CoV-2 recombinant RBD protein vaccine efficiently protected mice from SARS-CoV-2 in the animal challenge study. Therefore, IV-DOPE is considered an exceptional adjuvant for SARS-CoV-2 recombinant RBD protein-based vaccines and has the potential to be further developed into a SARS-CoV-2 recombinant RBD protein-based vaccine.